Конфликтологическая культура в старшем подростковом возрасте [Articol] - Ревенко, Оксана (CEP USM, 2022)
В статье анализируется содержание понятия «конфликтологическая культура личности». Описаны ее структурные компоненты: эмоционально-мыслительная культура, коммуникативная и поведенческая культура. Представлены результаты исследования по выявлению уровня развития конфликтной культуры и ее структурных компонентов у подростков. Также рассматриваются результаты гендерных различий в уровне развития конфликтной культуры в исследуемой выборке.

The article unravels the concept of „conflictological culture of personality" and describes its structural components: emotional and cognitive culture, behavioral and communicative culture. The article presents the results of research work into the level of development of conflictological culture and its structural components in late adolescence. It also analyzes the results of gender differences in the level of development of conflictological culture in the study sample.
CONFLICTOLOGICAL CULTURE IN LATE ADOLESCENCE
Keywords: конфликт; конфликтная культура личности; уровни и компоненты конфликтной культуры личности; подростковый возраст; гендерные различия; межличностный конфликт; conflict; conflictological culture of personality; adolescence; gender differences; interpersonal conflict